2010
DOI: 10.1063/1.3302139
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the semicylindrical solar tunnel dryer for drying handmade paper

Abstract: A walk in type semicylindrical solar tunnel dryer for drying 1500 handmade papers per batch has been commissioned at M/s Cellulosic Waste Recycling Education Project, Vidhya Bhawan Society, Udaipur, Rajasthan, India. A solar tunnel dryer with 122.95 m 2 solar collector area was sufficient for drying handmade paper from 53.85% to 9.96% moisture content ͑dry basis͒ in 4-5 h. In this paper the results are shown in terms of the variation of air temperature, solar flux density, relative humidity, air flow rate, moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several studies have been conducted by researchers to improve the performance of GHDs. Some of these advancements are their integration with PV modules [26,50,52,[70][71][72][73][74]; application of an opaque north wall to hamper heat loss from the dryer to ambient [75][76][77][78][79]; integration of thermal storage materials i.e., sand, phase change materials (PCMs), rockbed and black colored concrete floor [80][81][82][83]; integration of solar air heaters for faster drying [27,84]; and adding a supplementary area for drying area augmentation [85]. In this section, we discuss the most common technologies that are integrated with GHDs to improve their thermal efficiency, decrease the drying time, and increase the quality of the final product.…”
Section: Solar-assisted Greenhouse Dryers (Sghds)mentioning
confidence: 99%
“…Several studies have been conducted by researchers to improve the performance of GHDs. Some of these advancements are their integration with PV modules [26,50,52,[70][71][72][73][74]; application of an opaque north wall to hamper heat loss from the dryer to ambient [75][76][77][78][79]; integration of thermal storage materials i.e., sand, phase change materials (PCMs), rockbed and black colored concrete floor [80][81][82][83]; integration of solar air heaters for faster drying [27,84]; and adding a supplementary area for drying area augmentation [85]. In this section, we discuss the most common technologies that are integrated with GHDs to improve their thermal efficiency, decrease the drying time, and increase the quality of the final product.…”
Section: Solar-assisted Greenhouse Dryers (Sghds)mentioning
confidence: 99%
“…Drying. It has been found that about 68 per cent area of hemispherical shaped solar tunnel dryer towards south is able to receive sunlight whereas remaining 32 per cent area toward north is from the sun [11]. It is assumed that the overall thermal efficiency of solar tunnel dryer is 40 per cent.…”
Section: Collector Area Of Solar Tunnel Dryer Required Formentioning
confidence: 99%
“…The greenhouse is not limited to drying of agro products but also used for drying non-agro products like cotton, sludge, paper, rubber etc. [29][30][31][32]. The greenhouse operates usually in either active or passive modes.…”
Section: Introductionmentioning
confidence: 99%
“…as compared to drying under the open sun [21,40]. Various researches had taken place to improve the efficiency of greenhouse dryers like insulating north wall [29,30,[41][42][43], using mirrors for reflecting infrared radiations [44], using thermal storage material in floor [10,29,32,45,46], etc. The hybrid dryers are also a step towards the use of solar energy in a more effective manner and improving the productivity of greenhouses.…”
Section: Introductionmentioning
confidence: 99%